2019
DOI: 10.1093/ajcn/nqz097
|View full text |Cite
|
Sign up to set email alerts
|

Compound-specific isotope analysis reveals no retroconversion of DHA to EPA but substantial conversion of EPA to DHA following supplementation: a randomized control trial

Abstract: Background It has long been believed that DHA supplementation increases plasma EPA via the retroconversion pathway in mammals. However, in rodents this increase in EPA is likely due to a slower metabolism of EPA, but this has never been tested directly in humans. Objective The aim of this study was to use the natural variations in 13C:12C ratio (carbon-13 isotopic abundance [δ13C]) of n–3 PUFA supplements to assess n–3 PUFA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 53 publications
13
65
0
Order By: Relevance
“…Both DHA (22:6ω3) and EPA (20:5ω3) contributed to this increase in total ω-3 PUFA. The increase in EPA observed with DHA supplementation is consistent with published studies performed in vitro and in vivo [47,48].…”
Section: Dha Intake Increases ω-3 Pufa Content In Red Blood Cells Andsupporting
confidence: 91%
“…Both DHA (22:6ω3) and EPA (20:5ω3) contributed to this increase in total ω-3 PUFA. The increase in EPA observed with DHA supplementation is consistent with published studies performed in vitro and in vivo [47,48].…”
Section: Dha Intake Increases ω-3 Pufa Content In Red Blood Cells Andsupporting
confidence: 91%
“…However, evidence from both rats and human indicates that the increase in EPA is more likely because of a slower turnover of EPA in the plasma and liver, rather than the retro-conversion pathway of DHA to EPA [33,34]. Nevertheless, DHA feeding may slow the conversion of EPA to downstream metabolic products in the liver, with a concomitant decrease of DPA levels seen after DHA supplementation [33][34][35]. Taken together, the current data may suggest that the antidepressant-like effects of EPA better than DHA were possibly not through DHA, but rather due to EPA own function, either directly or via its metabolite DPA.…”
Section: Discussionmentioning
confidence: 99%
“…Retro‐conversion of DHA is more common in non‐neural cells than neural cells (Park et al, 2016). However, recently it was shown that increased plasma level of EPA in human following DHA supplementation did not occur via retro‐conversion rather a result of slowed metabolism and/or accumulation of plasma EPA (Metherel et al, 2019). During the last 30 years or so, the increasing incidence of several metabolic diseases are thought to be due to the results of high dietary intake of n‐6 fatty acid containing foods and oils compared with n‐3 fatty acids, thus increased the ratio of n‐6:n‐3 fatty acids (20:1) intake to a much higher level than the recommended ratio for optimal health benefits (Simopoulos, 2016).…”
Section: Dietary and Metabolic Sources Of Dha And Its Worldwide Consumentioning
confidence: 99%